The semiotics of desires in the Sufi experience according to Abu al-Qasim al-Junaid - Menacer, Souad; Kaouane, Mohamed (Journal of Human Sciences, 2023)
This article aims to know the identity dimentions in the miystical exprience according to Abi Elkassem Elanid (297 h) who is considered as one of the pioneers of Sufism who deeply studied the issue of annihilation and monotheism in the Sufic experience. These identity dimentions are the body of transcendence, Which wipe the drawing of creation in the divine being and acknowledge, His might and Lordship, Aadditionally, to search in those dimensions, semiotic saying of passions and its different procedures have been invested and applied on the sufic and Janid s text by interrogating the passions semiotically in an attempt to answer the following questions: What is the reality of the the sufi s experience according to the El Janid? How can the Sufic semiotic passions been attered by relying on the sayings of the semiotic passions?